2022
DOI: 10.3390/biology11060831
|View full text |Cite
|
Sign up to set email alerts
|

Community Vertical Composition of the Laguna Negra Hypersaline Microbial Mat, Puna Region (Argentinean Andes)

Abstract: The Altiplano-Puna region is a high-altitude plateau in South America characterized by extreme conditions, including the highest UV incidence on Earth. The Laguna Negra is a hypersaline lake located in the Catamarca Province, northwestern Argentina, where stromatolites and other microbialites are found, and where life is mostly restricted to microbial mats. In this study, a particular microbial mat that covers the shore of the lake was explored, to unravel its layer-by-layer vertical structure in response to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 123 publications
1
2
0
Order By: Relevance
“…Cyanobacteria were the most represented bacterial group, in agreement with previous observations in saline-alkaline lakes (Andreote et al, 2018). The other less representative Bacteria phyla (Bacteroidota, Patescibacteria and Chloroflexi) have been reported previously in microbialites (Couradeau et al, 2011), sediment samples of saline lakes (Vuillemin et al, 2018) and hypersaline microbial mats (Boidi et al, 2022;Vignale et al, 2021).…”
Section: Hierarchical Clustering Dendrogram and Nmds Based On Bray-supporting
confidence: 91%
“…Cyanobacteria were the most represented bacterial group, in agreement with previous observations in saline-alkaline lakes (Andreote et al, 2018). The other less representative Bacteria phyla (Bacteroidota, Patescibacteria and Chloroflexi) have been reported previously in microbialites (Couradeau et al, 2011), sediment samples of saline lakes (Vuillemin et al, 2018) and hypersaline microbial mats (Boidi et al, 2022;Vignale et al, 2021).…”
Section: Hierarchical Clustering Dendrogram and Nmds Based On Bray-supporting
confidence: 91%
“…Tamazawa et al (2012) indicated that ions (such as SO4 -2 ) could affect the morphology of microorganisms in the hot springs. The presence of ions may contribute to the complex range of colors in microbial mats (Boidi et al, 2022); this effect was observed in the microbial mats studied in the TG where various colors such as white, gray, yellow, red, pink, and green were observed, which coincides with the presence of sulfate ions, and other metals like Fe, Cd, Cu, Cr, and Al among others. org/10.22201/ib.20078706e.2023.94.5131 External factors can also influence the color of microbial mats.…”
Section: Discussionmentioning
confidence: 89%
“…Halorubrum and Natronomonas are known as aerobes (Mora-Ruiz et al, 2018), while Halapricum is a sulfate-reducing archaeon (Sorokin et al, 2022). Beside these genera from the dominant phyla, it is worth noting the presence of Halanaerobium (8.3%, representing 83.4% of the Halanaerobiaeota) and Truepera (8.5%, representing 99.8% of the Deinococcota), chemoorganotrophic strictly anaerobic and aerobic bacteria, respectively (Oren, 2015;Albuquerque et al, 2018), which are detected in hypersaline ecosystems (Boidi et al, 2022;Solchaga et al, 2022). Therefore, such observation indicated that the microbial community inhabiting the Salineta wetland is characteristic of extreme saline environments.…”
Section: Discussionmentioning
confidence: 97%